Características da deglutição em idosos comunitários e institucionalizados do município de Erechim/RS - Silva, Maria Augusta Flores da (2011)
Physiological mechanisms suffer chances during the aging process. Among these changes are the swallow difficulties. The integrity of swallow garantees the maintenance of the nutritional status of the patient, protecting the restiratory tract against accident as the aspiration of contents into the oropharynx. This article had the objective to study the swallow characteristics in communitarian elderly and residents of long period institution. The data collection was done in Erechim city/RS and the elderly were elected by the register in the national secretary of the health of the city and the resident were from a long stay house home of the elderly for that, were evaluated 160 elderly aged igual or more 60 years old divided in two groups: 80 communitarian and 80 elderly from the home of the elderly . The collect included a questionnaire, sensory motor evaluation, sensibility test, sensitivity taste test and clinical evaluation of swallow. The study permitted to conclude that institutionalized elderly presented less swallow difficulties in relation to the communitarian, this basically is due to the conditions evaluated between the two groups. The institutionalized elderly swallows slowly than the communitarian ones, allowing a better security in swallow.The changes in the food habit of eldery must be questioned by professionals who work with geriatric population and the clinic speech evaluation of swallow must be part of definition of the differential diagnosis in cases that show swallow difficulties and mainly in those which present pathologies which is related to dysphagia.